2014
DOI: 10.7554/elife.04601
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the ring formed by the tubulin homologue FtsZ in bacterial cell division

Abstract: Membrane constriction is a prerequisite for cell division. The most common membrane constriction system in prokaryotes is based on the tubulin homologue FtsZ, whose filaments in E. coli are anchored to the membrane by FtsA and enable the formation of the Z-ring and divisome. The precise architecture of the FtsZ ring has remained enigmatic. In this study, we report three-dimensional arrangements of FtsZ and FtsA filaments in C. crescentus and E. coli cells and inside constricting liposomes by means of electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
291
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 230 publications
(316 citation statements)
references
References 58 publications
(85 reference statements)
23
291
2
Order By: Relevance
“…We note that, in vitro, membrane-attached FtsZ can form long, continuous protofilaments (33,35) and that a recent ECT study observed long, single-layered protofilaments at cell division sites (35). These studies support a smooth, continuous Z-ring organization.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…We note that, in vitro, membrane-attached FtsZ can form long, continuous protofilaments (33,35) and that a recent ECT study observed long, single-layered protofilaments at cell division sites (35). These studies support a smooth, continuous Z-ring organization.…”
Section: Discussionsupporting
confidence: 59%
“…Active GTP hydrolysis may thus serve to constantly remodel the Z-ring, generating a discontinuous, clustered organization that can reorganize promptly in response to cellular cues. This GTPase-dependent remodeling may explain why long FtsZ protofilaments were more apparent with an overexpressed FtsZ variant with low GTPase activity (D212A) (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These experiments suggested that FtsZ and FtsA were sufficient to exert a significant inward pinching force on a membrane and could be doing so in the cell. Cryo-EM of inside-out Z ring complexes on liposomes displayed long parallel bundled filaments on the membrane [71,95], supporting the in vivo cryo-ET data. The second type of reconstitution comes from Martin Loose and Tim Mitchison, who investigated the interplay between purified FtsA and FtsZ on supported lipid bilayers (SLBs) [96].…”
Section: Reconstitution Of the Divisome On Membranes In Vitrosupporting
confidence: 75%
“…Such an arrangement is consistent with known interactions between FtsZ and its membrane anchor proteins such as FtsA (ZipA is absent in C. crescentus), which are lower in abundance than FtsZ and should periodically tether FtsZ polymers to the membrane. A more recent cryo-ET study also visualized long polymers, and more controls were done that suggested these polymers were FtsZ itself [71]. A major conclusion of this study was that the Z ring is comprised at least partially of continuous long FtsZ polymers, which seems to be at odds with the patchy nature of Z rings visualized by 3D-SIM and PALM.…”
Section: Viewing Native Divisome Structures By Cryo-electron Tomographymentioning
confidence: 58%